PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN SIKAP SISWA YANG DIBERI PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DENGAN TIPE THINK PAIR SQUARE PADA SMP NEGERI PEMATANGSIANTAR - Theresia Monika Siahaan (Universitas Islam Sumatera Utara, 2018)
Abstract. The aims of this research is (1) to know there is the diffrentiation of students' mathematical problem solving who teach between Kooperatif Think Pair Share and Think Pair Square, (2) to know there is the diffrentation of student’s attitude Kooperatif Think Pair Share and Think Pair Square, and (3) describe the process problem solving between cooperatif Think Pair Share and Think Pair Square. The research is kuasi eksperiment. The population of this research are all of students in SMP N Pematangsiantar, and the sample chosen is random, SMP Negeri 9 and SMP Negeri 3 Pematangsiantar with VII-4 and VII-5 as the eksperiment class 1 and VII-5 and VII-7 as eksperimen class 2 with 68 students every class eksperiment. This research uses two ways ANACOVA test. The results of this research shown that: (1) there is diffrentation in mathematical problem-solving from students who teach between Kooperatif Think Pair Share and Think Pair Square, (2) the atttitude of students who teach with kooperatif Think Pair Share better than the students who teach with Think Pair Square, and (3) the process of students answers who are taught with the Think Pair Share better than Think Pair Square. Keywords: Think Pair Share, Think Pair Square, Problem Solving Mathematical Ability, and Student’s Attitude